Influence of microstructure evolution on the dielectric properties of strontium titanate and alumina silicate - Leow, Chun Yan (2015)
Strontium Titanate (ST) and Alumina Silicate (AS) have wide range of applications as an advance ceramics. They are well known for their reliable performance especially at high temperature applications. Due to their amazing properties, most of the studies often focus on the after formation of its crystal structure phase and microstructure changes towards the dielectric properties. In fact, these studies are lacks of information link with the early stage of synthesis process. Wide range of sintering temperature and different particle size of green body must be set, in order to have a better understanding on the properties of ST and AS. In this study, a series of these samples were prepared by conventional solid-state reaction method with two different particle sizes (sieved with laboratory test sieve of size 45 μm and 20 μm). These samples undergo a sintering process at temperatures from 500°C to 1400°C at 100°C intervals. Across this sintering temperature range. Average grain size of the samples were measured to investigate the microstructure evolution. Field Emission Scanning Electron Microscopy (FESEM) was carried out to capture samples microscopic images while X-ray diffraction (XRD) analysis was to study and confirmed the formation of crystal structure phase of ST and AS. Average grain size changes and crystal structure formation were studied in parallel with the dielectric properties at various measuring temperatures. Dielectric properties of ST and AS were analyzed at two different frequency range. For low frequency dielectric measurement, the frequency range is at 40 Hz – 1 MHz at measuring temperature from 28°C to 300°C with 50°C interval. For microwave dielectric measurements, the frequency range is at 1 MHz – 1.8 GHz at room temperature.Based on XRD analysis, ST crystal structure started to form at 700°C sintering temperature. Synthesis was complete at 900°C. For AS, mullite compound was found and confirmed by XRD analysis at 1300°C and 1400°C sintering temperature. By observation, microstructure of ST started from agglomerated powder to form grains. As sintering temperature increases, grains continue to grow through the necking process. The evolution process is almost completed when grain boundaries diffuse with each other to form larger grains. By comparing both series of ST samples sintered at 1400°C, average grain size of the sample with greater starting particles size is 0.640 μm while another is 0.496 μm. ST45 (sieved with test sieve of 45 μm) was experiencing rapid grain growth at the final sintering stage, while ST20 (sieved with test sieve of 20 μm) grain growth was slower. For AS, thin and long rectangular shape grain structure were observed in samples sintered at 1400°C. ST samples with greater starting particles size form larger grain size. At low frequency measurement, dielectric constant is dependent on frequency. Grain size will alter the dielectric constant of ST depending on the measuring temperatures. Loss tangent, tan δ is also dependent on measuring temperature. Loss peak are strongly connected with frequency and measuring temperature. Agglomerations of powders will encourage alternating current conduction at high measuring temperature and causing the dielectric constant to drop. Dielectric constant of ST20 is greater than ST45 due to greater interfacial polarization effects occurred in ST20. ST20 has smaller grain size that would increase its surface effect. Rapid grain growth in ST45 had reduces its dielectric properties performances. Slower grain growth is important to promote homogeneous grain size and grains distribution during ST microstructure evolution. Homogeneous and smaller particle size are important factors to form high quality ST ceramic with good dielectric properties. For microwave frequency measurement, when frequency is beyond 107 Hz, dielectric constant value will remains constant across increasing frequency. Dielectric properties of ST is dependent of the grain size. ST with complete crystal structure will show greater dielectric constant value.